2005
DOI: 10.1073/pnas.0506130103
|View full text |Cite
|
Sign up to set email alerts
|

Complementary base-pair-facilitated electron tunneling for electrically pinpointing complementary nucleobases

Abstract: Molecular tips in scanning tunneling microscopy can directly detect intermolecular electron tunneling between sample and tip molecules and reveal the tunneling facilitation through chemical interactions that provide overlap of respective electronic wave functions, that is, hydrogen-bond, metal-coordination-bond, and charge-transfer interactions. Nucleobase molecular tips were prepared by chemical modification of underlying metal tips with thiol derivatives of adenine, guanine, cytosine, and uracil and the outm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 35 publications
(44 reference statements)
6
96
1
1
Order By: Relevance
“…Certainly, the exquisite ability of (context independent) stochastic sensing to distinguish between molecules (14,49) shows what can be done with nanopores under the most favorable conditions. In the case of solid-state nanopores, it has been suggested that an active property of translocating bases (such as the ability to carry tunneling currents) might be used for sequencing (10,(50)(51)(52), but no practical demonstration of such a technique has been made. Another obvious requirement of a strand sequencing system is an ability to ''count'' bases.…”
Section: Single-nucleotide Discrimination Within a Heteropolymeric Sementioning
confidence: 99%
“…Certainly, the exquisite ability of (context independent) stochastic sensing to distinguish between molecules (14,49) shows what can be done with nanopores under the most favorable conditions. In the case of solid-state nanopores, it has been suggested that an active property of translocating bases (such as the ability to carry tunneling currents) might be used for sequencing (10,(50)(51)(52), but no practical demonstration of such a technique has been made. Another obvious requirement of a strand sequencing system is an ability to ''count'' bases.…”
Section: Single-nucleotide Discrimination Within a Heteropolymeric Sementioning
confidence: 99%
“…The ultimate speed of such a technology is difficult to assess at this point, because it is not only determined by the actual readout process. Lindsay and coworkers 47,48 have estimated the possible read rate to be on the order of 10 bases, based on an estimate of the residence time of the bases in their tunnelling junction, the statistical confidence level required to assign the identity of a base and the translocation force in the nanopore obtained in the previous work by Keyser et al 88 and van Dorp et al 89 Note that the force measurements by Keyser et al 88 were performed on doublestranded λ-DNA, and not single-stranded oligonucleotides used in the Lindsay experiment. This may change the magnitude of the force, but is unlikely to change the qualitative picture.…”
Section: Small-molecule Sensing By Tunnelling Currentsmentioning
confidence: 99%
“…It appears that the former can cause complex current burst characteristics, which in turn contain valuable information about the molecular process itself, for example, hydrogen-bonding patterns (recognition tunnelling) 45 47,48 and the 'free-analyte' configuration where a freely diffusing analyte bridge binds to each adapter at the same time, thus bridging the tunnelling gap. In both cases, recognition events result in distinct and well-defined modulation of the tunnelling current, in terms of magnitude, event frequency and other details of the tunnelling noise.…”
Section: Dynamic Interfacial Processes Probed By Tunnelling Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Ohshiro and Umezawa [12] has shown that hydrogen bonds can facilitate electron tunneling so that tunneling current decays more slowly when it is formed between a Watson-Crick complementary base pair compared to a non-complementary base pair. Also, the electron-tunneling property of different base pairs (G-C, A-T, G-T, and 2AA-T) has been investigated by Lee et al [13] with methods of complex band structure and Green's function scattering theory for I-V characteristics, showing that as more hydrogen bonds are formed between the DNA bases, higher conductance can be observed, and the decay factor for a unit cell of base pair will increase as the hydrogen bond distance increases with a linear relationship.…”
mentioning
confidence: 99%